Muscular Performance and Blood Pressure After Different Pre-Strength Training Strategies in Recreationally Strength-Trained Women: Cross-Over Trial - Estêvão Rios Monteiro; Linda S. Pescatello; Luis Leitão; Marcelo José Colonna de Miranda; Paulo H. Marchetti; Michelle Ribeiro Novaes; Gleisson da Silva Araújo; Victor Gonçalves Corrêa Neto; Jefferson da Silva Novaes (Journal of Cardiovascular Development and Disease)
Background: This study aimed to investigate the acute effects of different pre-ST strategies on muscular performance and blood pressure (BP) responses in recreationally strength-trained women. Methods: Twelve overweight women with normal BP were recruited and performed six experimental protocols in a randomized order: (1) control protocol (CC), where BP was assessed without exercises performed; (2) ST; (3) foam rolling warm-up followed by ST (FR + ST); (4) specific warm-up followed by ST (SW + ST); (5) aerobic exercise followed by ST (AE + ST); and (6) stretching exercises followed by ST (SE + ST). ST consisted of three sets at 80% of 10 repetition maximum with a self-suggested rest interval between sets for bench press, back squat, bench press 45°, front squat, lat pull-down, leg press, shoulder press, and leg extension. Results: All experimental protocol had a lower total training volume, fatigue index, and repetitions performance in relation to ST (p < 0.05). No significant reduction was observed in systolic and diastolic BP for any protocol or exercise, although the effect size magnitudes ranged from trivial to large. Decreases in maximum repetitions, resistance to fatigue, and total training volume were performed before ST as warm-up strategies. However, these strategies indicated a clinical reduction in BP with a large and meaningful magnitude (effect size) in recreationally strength-trained women with normal to elevated BP. Conclusions: The results of this investigation may help to influence decision-making by practitioners who desire to elicit a post-exercise hypotension response in both subjects with normal BP and hypertension.